THE CONCEPT OF «PEDAGOGICAL ACTIVITY» IN LEGISLATION AND LAW PRACTICE: A COMPREHENSIVE ANALYSIS OF THE CONTENT - USACHEVA ELENA (Legal Bulletin, 2025)
The relevance of the research is related with the lack of a unified approach to the qualification of pedagogical activity in Russian educational legislation and legal doctrine.